New Insights on the UV/TiO2 Photocatalytic Treatment of Thiomersal and its 2-Sulfobenzoic Acid Product - De La Fournière, Emmanuel M. (2021)
Background: Thiomersal (TM), a complex between 2-mercaptobenzoic acid (2-MBA) and ethylmercury (C2H5Hg+), is an antimicrobial preservative used in immunological, ophthalmic, cosmetic products, and vaccines. Objective: TM has been treated by UV/TiO2 photocatalysis in the presence or absence of oxygen at acidic pH. C2H5Hg+, 2-MBA, and 2-sulfobenzoic acid (2-SBA) were found as products. A 2-SBA photocatalytic treatment was undertaken to study sulfur evolution. Methods: Photocatalytic runs were performed using a UVA lamp (λmax = 352 nm), open to air or under N2. A suspension of the corresponding TM or 2-SBA salt and TiO2 was prepared, and pH was adjusted. Suspensions were stirred in the dark for 30 min and then irradiated. TM, 2-MBA, 2-SBA, and C2H5Hg+ were quantified by HPLC, sulfur by TXRF, and the deposits on the photocatalyst were analyzed by chemical reactions. The mineralization degree was followed by TOC. Sulfate was determined using BaCl2 at 580 nm. Results: Photocatalytic destruction of TM and total C2H5Hg+ was complete under N2 and air, but TM degradation was much faster in air. The evolution of TM and the products followed a pseudo-first order kinetics. Conclusion: TiO2-photocatalytic degradation is a suitable technique for the treatment of TM and its degradation products. In contrast to other organomercurial compounds, TM degradation is faster in the presence of O2, indicating that the oxidative mechanism is the preferred pathway. A significant TM mineralization (> 60%, NPOC and total S) was obtained. TM was more easily degraded than 2-SBA. Sulfate was the final product.